Investigation on Psyllium Gum as a Bio-Based Binder for Silicon Anode in Lithium-Ion Batteries - ARCA, EMİN (My University, 2024)
Silicon (Si) anode is of considerable interest in Li-ion batteries due to its high theoretical capacity (4200 mAh g−1), abundant reserves in the earth, and environmentally friendly nature. Although Si anode has significant advantages, the electrode is prone to cracks due to large volume changes in its structure during discharge cycles in Li-ion batteries. Rapid capacity degradation occurs as a result of deterioration of the structural integrity of the electrode. Although binders are known to contribute to improving the electrochemical performance of anode materials, polyvinylidene fluoride (PVdF) used in commercial Li-ion batteries cannot maintain the mechanical stability of the Si anode during cycles due to weak Van der Waals interactions, which also dissolves in the flammable, explosive and volatile solvent N-Methyl-2-pyrrolidone (NMP). In this study, low cost, sustainable and environmentally green psyllium gum (PG) was extracted from psyllium husk and tested for the first time as a water-soluble binder for Si anode. According to galvanostatic charge/discharge tests, the Si-PG anode exhibits a capacity of 1415 mAh g−1 after 100 cycles at a voltage range of 0.01–1.5 V and current density of C/2, which is almost 3 times higher than the Si-PVdF anode (494 mAh g−1).
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; Mühendislik Bilişim Ve Teknoloji (Eng); Temel Bilimler (Sci); Mühendislik; Mühendislik Kimyasal; Engineering Computing & Technology (Eng); Natural Sciences (Sci); Engineering; Engineering Chemical; Kataliz; Fizik Bilimleri; Catalysis; Physical Sciences; Electrochemical performance; Li-ion battery; Psyllium gum binder; Silicon anode